PENDAKIAN DI JAWA TENGAH : MOTIVASI EKOWISATA DAN PERILAKU WISATAWAN - Sabila, Fadlilaili Whahda; Purwanti, Evi Yulia (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
High interest in hiking is influenced by tourist behavior, so that it will potentially increase negative impact due to tourist activities in vulnerable areas. Tourist behavior in decision making can be estimated through the demand side of hiking. This research aims to analyze the factors that influence number of individual visits to the hiking sites in Central Java. The result showed seven variables influence the number of individual visits to hiking sites, those are physical motivation, landscape value, natural value, tourist facilities, accessibility, travel cost, and other tourism site. In the development of mountain-based tourism should pay attention to the alignment of tourism aspects and ecotourism principles.